2011
DOI: 10.1177/082585971102700402
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved Family Members’ assessments of the quality of End-Of-Life Care: What is Important?

Abstract: Families of patients are well poised to comment on the end-of-life (EOL) care received by those patients and can provide feedback to care providers and decision makers. To better understand family-member evaluations of the quality of in-patient EOL care, this study draws on qualitative interview data (n=24) to identify core aspects of EOL care that are important for family members. Based on this analysis, a conceptual framework of family members’ assessments of their experiences with EOL health care services i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…Research suggests healthcare providers and family members may perceive emotional and spiritual support differently. Health service providers tend to view the offer of support in the form of relational and active-based care whereas family and caregivers view supportive care as having conversations and shows of regard [35,48]. …”
Section: Discussionmentioning
confidence: 99%
“…Research suggests healthcare providers and family members may perceive emotional and spiritual support differently. Health service providers tend to view the offer of support in the form of relational and active-based care whereas family and caregivers view supportive care as having conversations and shows of regard [35,48]. …”
Section: Discussionmentioning
confidence: 99%
“…The comments made by families also highlight one of the key complexities of family support—how families choose to interpret what care their loved one is or is not given [7]. Many families will interpret positive or negative experiences of caring “for” as the more personal caring “about” the person—something that many caregivers do not keep uppermost in mind when they are dealing with patients and families.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, questionnaires to assess the dying experience in bereaved relatives have been validated [5] and used to measure care [6]. A recent review of the literature of family satisfaction with EOL care [7] has identified key domains of EOL care: Patient comfort and symptom management, emotional support, information and education; communication and competence have been identified by quantitative studies. Qualitative studies have revealed more complex indicators such as care provider response and time with patient; providers’ interactional approach; service coordination, consistency and flexibility; personalized and individual care; and the facility environment.…”
Section: Introductionmentioning
confidence: 99%
“…The third dataset was from a qualitative study of 24 bereaved family caregivers whose family member died in an inpatient setting. 48,49 Participants were recruited from a larger sample of 388 respondents to a quantitative, mailed questionnaire, which examined family members' perceptions of the quality of palliative care received in an inpatient setting. 50 The 24 participants were asked in interviews to describe and evaluate their experience with the palliative care received by the deceased person.…”
Section: Methodsmentioning
confidence: 99%